Alpha-lipoic acid alleviates oxidative stress and brain damage in patients with sevoflurane anesthesia - Gao, Kailun; Wu, Ying; Zhang, Yan; Dang, Pei; Xue, Huanjia; Li, Teng; Zhou, Meiyan; Wang, Liwei; Zhu, Yangzi (Frontiers in Pharmacology, 2025)
Sevoflurane, the most commonly used inhalational anesthetic, may negatively impact the brain by inducing oxidative stress. This study investigated the potential protective role of alpha-lipoic acid (ALA) in mitigating sevoflurane-induced oxidative stress and brain damage. A total of 155 patients undergoing sevoflurane anesthesia for liver resection surgery were randomly assigned to receive either ALA or a placebo. Perioperative internal jugular venous blood samples were collected to measure oxidative stress markers (8-OHdG, sORP, and cORP) and brain injury biomarkers (S100β and UCH-L1). Postoperative cognitive function was also evaluated. The results demonstrated that, compared to the placebo group, the ALA group exhibited a significant reduction in 8-OHdG levels by 0.007 nmol/L (95% CI, −0.011 to −0.003; P = 0.03) 24 h after surgery, accompanied by lower sORP levels and higher cORP levels. Furthermore, postoperative levels of S100β and UCH-L1 were significantly lower in the ALA group than in the placebo group (S100β, P = 0.02; UCH-L1, P = 0.03). Additionally, oxidative stress markers were significantly correlated with brain damage 24 h after surgery. Our findings suggest that ALA significantly reduces sevoflurane-induced oxidative stress and brain damage, while also improving postoperative cognitive function, indicating its potential neuroprotective effect.Clinical Trial Registration:https://www.chictr.org.cn/, identifier ChiCTR2300077321.